Non-equilibrium solidification and microsegregation in centrifugally cast high speed steel for rolls - Klančnik U.; Košec B.; Mrvar P.; Medved J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
When regarding as-cast microstructures of highly alloyed metals, microsegregation of alloying elements is a common feature resulting from non-equilibrium conditions during solidification. The aim of this work is to predict the occurrence and severity of microsegregation in highly alloyed, centrifugally cast high speed steel used for rolls. The prediction was performed using thermodynamic Scheil-Gulliver modelling with Thermo-Calc software. The modelled predictions were then compared with differential scanning calorimetry, X-ray diffraction, light and electron microscopy with energy dispersive spectroscopy, all performed on an as-cast roll shell. Results show that chromium, molybdenum and vanadium have the highest tendency to microsegregation. Vanadium tends to form negative microsegregation, while molybdenum and chromium form positive microsegregation. Scanning electron microscopy revealed the presence of complex eutectic carbides, confirming the Scheil-Gulliver non-equilibrium solidification path via two main successive eutectic reactions.